Perlindungan Hukum Bagi Kurir dalam Sistem Cash on Delivery Belanja Online - Riska Natagina Putri; Siti Nurul Intan Sari Dalimunthe (Faculty of Sharia, Islamic State University (UIN) Prof. K.H. Saifuddin Zuhri Purwokerto, Indonesia, 2021)
This study aims to find out the legal position of the couriers in online shopping activities, especially in the payment method of COD (Cash on Delivery); the legal protection that can be given to the COD couriers; and the legal protection for the couriers who encounter buyers who default and refuse the goods they ordered. The method used in this research is the normative juridical method by examining library materials or secondary data sources, namely laws and regulations, books, and legal studies. Based on this method, the research was conducted using a statutory approach and a case approach. The results show that the legal position of the couriers in the online shopping with COD method of payment is as a recipient of a deposit, as a person who represents a freight forwarder in carrying out the power of attorney from the seller, and as a recipient of payment from the buyer. The legal protection that can be given to the couriers is ensuring that the couriers are not responsible for any discrepancy or damage to goods that are not caused by his mistake or negligence.